Reactive oxygen species-induced toxicity and mutants in chinese hamster ovary cells - Salazar, Mames J.; Hsie, Abraham W. (Actualidades Biológicas, 2017)
The chinese hámster ovary (CHO) cell system is widely used system to study spontaneous and induced-toxicity and mutagenicity in mammalian cells. By comparing toxicity and mutation spectrum of identically exposed repair proficient and repair-deficient cell lines, the possible roles of DNA repair in toxicity may be defined. In this study we propose that parental CHO-K1-BH4 is more resistant to oxidative damage caused by hydrogen peroxide (H3O2), added directly to the medium or generated steadily by glucose oxidase (Go), paraquat and xanthine oxidase (XO) than its derivatives AS52 and XRS-5. We hypothesize that the various CHO cell lines differ in sensitivity to oxidative damage and that the observed toxicity may be due to accumulation of DNA breaks and impairment of the mitochondrial functions. High toxicity was observed (low clonogenic survival) for all tested compounds in all cell lines. Line XRS-5 seemed to be more sensitive to reactive oxygen species (ROS)-induced toxicity. CHO-K1-BH4 parental cell line appeared to be more resistant to the compounds studied when compared to the radiosensitive XRS-5 cell line. Glucose oxidase (4mU/ml) resulted equitoxic to parental and derivatives cell lines, 500 mM of H3O2 Increased ~4 fold the mutant frequency above the background in AS52. Xanthine oxidase (100 mU/ml) increased ~4 fold the mutagenicity frequency in XRS-5. None of the other tested compounds induced 6-TG resistance as mutagenic response. This difference may be due to different ability to handle oxidative damage associated with genetic composition and repair enzymatic responses.